Use of olive leaf extract to reduce lipid oxidation of baked snacks. (June 2018) - Difonzo, Graziana; Pasqualone, Antonella; Silletti, Roccangelo; Cosmai, Lucrezia; Summo, Carmine; Paradiso, Vito M.; Caponio, Francesco
Abstract: Olive leaves are a waste of the olive oil processing industry and represent a good source of phenolic compounds. The aim of this work was to assess the influence of olive leaf extract (OLE) on lipid oxidation of baked snacks, like breadsticks, made with wheat flour, extra virgin olive oil (EVO), white wine, and salt. Two EVOs having different peroxide value and antioxidant profile (total phenol content, tocopherols, carotenoids, and antioxidant activity) were considered. The snacks were subjected to oven test or stored in the usual conditions of retailer shelves. The obtained data highlighted that EVO plays a key role both for the quality and for the shelf-life of baked snacks and the use of OLE is recommended especially when baked snacks are produced with low quality EVO which therefore does not have a good content of natural antioxidants. The OLE addition significantly reduced the forced oxidative degradation during oven test, as evidenced by a decrease of 27% in oxidation-related volatile compounds and of 42% in triacylglycerol oligopolymers compared to control snacks (CTR) without OLE. Moreover, OLE effectively acted also in normal storage conditions, improving sensory data, induction times, antioxidant activity, and volatile compounds compared to CTR (i.e. hexanal 165.49 vs 38.31 μg g −1 in OLE-added). The amount of oxidation-related volatile compounds showed an opposite trend with the quality level of oil used. Graphical abstract: Unlabelled Image Highlights: Olive leaf extract (OLE) showed antioxidant activity in baked snacks. EVO plays a key role for the quality and for the shelf-life of baked snacks. Lipid oxidation was influenced by both the OLE addition and the EVO quality. OLE is recommended especially in baked snacks made with low quality EVOs.